Does point-of-care ultrasound examination by the general practitioner lead to inappropriate care? A follow-up study - Camilla Aakjær Andersen; John Brandt Brodersen; Jan Mainz; Janus Laust Thomsen; Ole Graumann; Thomas Løkkegaard; Martin Bach Jensen (Scandinavian Journal of Primary Health Care)
Background The use of point-of-care ultrasound (POCUS) in general practice increases, but little is known about potential unintended findings and harms to patients. Information regarding such unwanted effects may be obtained by evaluating the medical records of patients who have been scanned by their general practitioner.Objective To identify and characterize re-consultations related to POCUS use in general practice, potential misdiagnosis, overdiagnosis, and incidental findings, and to compare potentially troublesome cases to GPs’ scanning competence and type of ultrasound device.Design and Setting Professors in general practice with extensive experience in both research and quality assurance in general practice did a blinded review of prospectively collected routine electronic medical record data combined with cross-sectional data collected in relation to POCUS examinations.Subjects Twenty general practitioners collected data on 564 patients examined with POCUS in primary care.Main Outcome Measures International standards for the classification of adverse events and incidental findings were used. First, research assistants identified all re-consultations described in the medical records that were related to the primary health complaint at the index consultation. Second, these re-consultations were classified by the medical experts in terms of seriousness and relation to the POCUS examination performed at the index consultation. In addition, the experts identified possible misdiagnosis, possible overdiagnosis, and incidental findings. Finally, identified cases were discussed in terms of appropriateness and described narratively.Results Medical records of 564 patients were reviewed. A low risk of possible misdiagnosis (5.3%), potential overdiagnosis (0.7%), and incidental findings (0.7%) were found. Eleven POCUS-related re-consultations were identified and described.Conclusion POCUS scanning performed by general practitioners was generally safe, but it can result in unnecessary examinations and potential harm in a few cases. Certain areas, e.g. pelvic scans that included the ovaries, may especially be prone to misdiagnosis.Trial Registration Number NCT03375333